T follicular helper (Tfh) cells in normal immune responses and in allergic disorders. Issue 8 (25th May 2016) - Varricchi, G.; Harker, J.; Borriello, F.; Marone, G.; Durham, S. R.; Shamji, M. H.
Abstract: Follicular helper T cells (Tfh ) are located within germinal centers of lymph nodes. Cognate interaction between Tfh, B cells, and IL‐21 drives B cells to proliferate and differentiate into plasma cells thereby leading to antibody production. Tfh cells and IL‐21 are involved in infectious and autoimmune diseases, immunodeficiencies, vaccination, and cancer. Human peripheral blood CXCR5 + CD4 + T cells comprise different subsets of Tfh ‐like cells. Despite the importance of the IgE response in the pathogenesis of allergic disorders, little is known about the role of follicular and blood Tfh cells and IL‐21 in human and experimental allergic disease. Here, we review recent advances regarding the phenotypic and functional characteristics of both follicular and blood Tfh cells and of the IL‐21/IL‐21R system in the context of allergic disorders.